(untitled) (Jurnal Ipteks Terapan, 2022)
The mapping of tourism potential in the village of kumpulrejo is important for the development of pioneering tourism villages. The tourist attraction of Kumpulrejo village as a tourist destination is tani rukun santosa group and coffee plantation. The pioneering development of the kumpulrejo tourism village requires creative efforts to create and issue a unique character. Kumpulrejo Village is one of the pioneering tourism villages in the city of Salatiga, Argomulyo district. The community service activity is a collaboration of the STIEPARI Semarang service team with the Salatiga city government to support the tourism development program of the city of Salatiga as a gastronomy city. The purpose of this service is to map the tourism potential of the kumpulrejo village and map the strategies that need to be done to become an agriculture-based tourism village. With the mapping of the tourism potential of Kumpulrejo village, it is hoped that this roadmap will be the first step in developing the Kumpulrejo tourist village.